Pembelajaran Musik Ansambel Tradisional Minangkabau di SMP Angkasa Lanud Padang - Febri Yelmi; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2022)
This study aims to describe how the Implementation of Minangkabau Traditional Ensemble Music Learning at SMP Angkasa Lanud Padang. The type of descriptive qualitative research is a research method that describes the findings in the field by describing the things to be studied in the form of words. The data collection technique is from direct observation or observation of how the implementation of Minangkabau traditional ensemble music learning, then interviews with related parties, literature studies and documentation as data collection in the process of implementing Minangkabau traditional ensemble music learning. The results of the study at the time of the implementation of Minangkabau traditional ensemble music learning did not show maximum results in the application of the learning process because based on observations not everything was carried out following the learning design that had been made by the teacher. In practice, the teacher is not fully able to play the traditional musical instrument talempong rea itself. Such a short time makes the practice process ineffective. Students only know how to play talempong musical instruments and cannot fully play talempong rea music in groups. Due to the lack of mastery of the material and the limited use of tools owned at school.